Impact of Nicotine Replacement Therapy Sampling on Cessation-Related Processes. - Sisson, Michelle L.; Gajos, Jamie M.; Wolford-Clevenger, Caitlin; Chichester, Keith R.; Hawes, Elizabeth S.; Hill, Samantha V.; Shelton, Richard C.; Hendricks, Peter S.; Businelle, Michael S.; Carpenter, Matthew J.; Cropsey, Karen L. (Journal of Addiction Medicine)
Objectives: Smoking prevalence remains high among low-income smokers. Understanding processes (eg, withdrawal, craving, motivation) in early smoking cessation is crucially important for designing effective interventions for this population. Methods: This is a secondary analysis of a novel, in-session sampling intervention (ie, In Vivo) as compared with standard care behavioral smoking cessation counseling (SC) among community-dwelling low-income smokers (n = 83). This analysis examined the effect of 5 in-session sampling interventions on cessation-related processes and perceived advantages or disadvantages of nicotine replacement therapy (NRT) products over time using daily diaries. Results: The In Vivo treatment had an early positive impact in terms of decreasing withdrawal symptoms and cravings, and increasing perceived advantages to NRT, with moderate to large effect sizes. Results also showed that the treatment effectively reduced withdrawal symptoms and cravings in-session, with small-to-medium and medium-to-large effect sizes, respectively. In-session reduction of withdrawal symptoms and cravings did not occur for the SC group, with the exception of decreased withdrawal symptoms occurring during week 4. The In Vivo treatment did not impact quit goal, desire to quit, abstinence self-efficacy, perceived difficulty in quitting, motivational engagement, or perceived disadvantages to NRT. The In Vivo group reported less daily cigarette use relative to the SC group, in addition to reporting less cigarette use on days they reported greater combination NRT use. Conclusions: There is preliminary support for this In Vivo treatment over SC in reducing withdrawal, craving, and the number of cigarettes smoked per day, as well as promoting perceived advantages of NRT among low-income smokers.